Decay resistance of extractive-free belian (eusideroxylon zwageri) and malagangai (potoxylon melagangai) - Jusoh, Ismail; Isa, Ipor (Forestry & Forest Products Research, 2004)
Belian (Eusideroxylon z.wagen) and malagangai (Potoxylon melagangai) are among the heaviest and very durable timbers ofMalaysia and Indonesia. It is well known that the natural durability of timbers is influenced by their extractives content. This study was earned out to determine the decay resistance of extractive-free E. z.wageri and P. melagangai wood. Heartwood and sapwood ofE. z.wageri and P. melagangai were cut into test blocks of 2 em x 2 em cross-section and 5 mm thickness. Extractives were extracted using Soxhlet apparatus. The four wood decay fungi used in this study were three white-rot fungi, Lentinus sajor-caju, Trametes versicolor and Pycnoporus sanguineus and one brown-rot fungus, Gloeophyllum trabeum. Wood decay was assessed based on weight loss after 12 weeks exposure in the soil block test. Test blocks exposed to P. sanguineus resulted in higher weight loss than those exposed to C. trabeum. Sapwood and heartwood of E. z.wageri showed higher decay resistance compared with P. melagangai. Extractive-free blocks had higher weight losses than the unextracted blocks. Although extraction of extractives significantly reduced decay resistance of both wood species, the extractive-free blocks could still be considered resistant. This study showed that the high resistance ofE. z.wageri and P. melagangai to decay is due to the presence of toxic extractives. However, extractives are not the sole factor contributing to decay resistance of both wood species.